US’ TAIWAN STRATEGY: AN INSTRUMENT TO CONTAIN CHINA - Farooq, Muhammad (Margalla papers, 2023)
The issue of Taiwan has become a major point of contention between the US and China, with visits by US officials resulting in strong criticism from China and military escalation in the region. Experts are concerned that a conflict between these two powers in the Asia-Pacific region could endanger global peace and stability, especially given the ongoing Russia-Ukraine conflict. China maintains its claim over Taiwan under the 'One China Policy,’ considering it a lost province and advocating for its unification with the mainland. While recognising Taiwan as part of China under this policy, the US engages in diplomatic and military activities with Taiwan, which China considers interference in its internal affairs. In the post-Cold War era, the US adopted an ambiguous policy towards Taiwan as part of its containment strategy against China. Therefore, the US seeks to slow China's perpetual growth by promising enhanced defence for Taiwan. Recent US official visits to Taiwan reflect provocative measures in line with this strategy. This paper analyses the US' Taiwan policy as a containment instrument against China, recent measures adopted by the US administration to provoke China, Taiwan's strategic significance, and the US' long-standing commitment to Taiwan's security as essential for maintaining its leadership role in international affairs.